PERAN ASEAN INTERGOVERNMENTAL COMMISSION ON HUMAN RIGHTS SEBAGAI INSTITUSI HAM ASEAN: KASUS ROHINGYA DI MYANMAR 2012-2016 - Oddie Bagus Saputra; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
This research explains and analyzes the role of the AICHR as an ASEAN Human Rights Institution in its engagement in the Rohingya case in Myanmar for the period 2012-2016. The purpose of this research is to explain the causes of human rights violations against Rohingya ethnicities, the involvement of the AICHR in that case and the obstacles faced by AICHR in their involvement. This research uses qualitative research methods to provide answers by describing the facts related to Rohingya case and the AICHR’s efforts to get involved in the case. The frame of mind used in this study is the paradigm of Institutional Liberalism, concept of International Organization, and concept of International Regime. Researcher found that the involvement of AICHR in the Rohingya case was limited to being used as a forum or meeting place for its member countries to discuss and gather information regarding the case. This is due to the presence of internal AICHR factors including limited authority or mandate, lack of independence of members and an inefficient and effective consensus system. Meanwhile, external factors originated from the application of the ideology of socialism by Myanmar which caused this country to become closed so that AICHR had difficulty in obtaining and collecting information related to the Rohingya case.